2006
DOI: 10.1007/s11120-006-9086-4
|View full text |Cite
|
Sign up to set email alerts
|

Redox properties of the Rhodobacter sphaeroides transcriptional regulatory proteins PpsR and AppA

Abstract: Redox properties of the photosynthetic gene repressor PpsR and the blue-light photoreceptor/antirepressor AppA from Rhodobacter sphaeroides have been characterized. Redox titrations of PpsR reveal the presence of a two-electron couple, with an E (m) value of -320 mV at pH 7.0, which is likely to arise from the reversible conversion of two cysteine thiols to a disulfide. This E (m) value is very much more negative than the E (m) = -180 mV value measured previously at pH 7.0 for the disulfide/dithiol couple in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…If we assume redox equilibrium between GSH/GSSG and the regulatory proteins included in Fig. 4, both RegB (E m ϭ Ϫ294 mV [32]) and PpsR (E m ϭ Ϫ320 mV [18]) would be Ͼ90% in the oxidized disulfide form over the 35-mV span of GSH/GSSG in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…If we assume redox equilibrium between GSH/GSSG and the regulatory proteins included in Fig. 4, both RegB (E m ϭ Ϫ294 mV [32]) and PpsR (E m ϭ Ϫ320 mV [18]) would be Ͼ90% in the oxidized disulfide form over the 35-mV span of GSH/GSSG in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…PpsR in R. sphaeroides controls heme, bacteriochlorophyll, and photosynthesis gene expression with the activity of the PpsR-AppA system highly regulated by numerous input signals such as light, redox, and heme (1, 7, 8). Several input signals directly affect the activity of PpsR, while others affect the ability of AppA to interact with PpsR.…”
Section: Introductionmentioning
confidence: 99%
“…AppA is an antagonist of PpsR, a transcriptional repressor of photosynthetic genes, which regulates photosystem synthesis in response to oxygen concentration and bluelight intensity in the purple bacterium Rhodobacter sphaeroides. [4][5][6][7][8][9][10][11] AppA has at least two separate domains, an N-terminal flavin-binding BLUF domain and a C-terminal Cys-rich region where PpsR may be bound under dark conditions. It is suggested that the light state BLUF domain of AppA associates with the AppA C-terminal region to inhibit the interaction of AppA and PpsR.…”
mentioning
confidence: 99%
“…AppA inhibits the DNA-binding activity of PpsR by two mechanisms: (1) through reduction of a specific intramolecular disulfide bond in oxidized PpsR and (2) through complex formation between reduced AppA and reduced PpsR. 9,11 Here, to observe the mutational effects for only blue-light control (but not redox control) of AppA activity, the gel mobility shift assays were carried out in the presence of dithiothreitol to reduce all dithiol/ disulfide pairs in AppA and PpsR. Under the reduced conditions, AppA makes a complex with PpsR in the dark to inhibit DNA binding.…”
mentioning
confidence: 99%